Global Repetition Influences Contextual Cueing - Zang, Xuelian; Zinchenko, Artyom; Jia, Lina; Assumpção, Leonardo; Li, Hong (Frontiers in Psychology, 2018)
Our visual system has a striking ability to improve visual search based on the learning of repeated ambient regularities, an effect named contextual cueing. Whereas most of the previous studies investigated contextual cueing effect with the same number of repeated and non-repeated search displays per block, the current study focused on whether a global repetition frequency formed by different presentation ratios between the repeated and non-repeated configurations influence contextual cueing effect. Specifically, the number of repeated and non-repeated displays presented in each block was manipulated: 12:12, 20:4, 4:20 and 4:4 in Experiments 1-4 respectively. The results revealed a significant contextual cueing effect when the global repetition frequency is high (≥ 1:1 ratio) in Experiments 1, 2 and 4, given that processing of repeated displays was expedited relative to non-repeated displays. Nevertheless, the contextual cueing effect reduced to a non-significant level when the repetition frequency reduced to 4:20 in Experiment 3. These results suggested that the presentation frequency of repeated relative to the non-repeated displays could influence the strength of contextual cueing. In other words, global repetition statistics could be a crucial factor to mediate contextual cueing effect.